2021
DOI: 10.1016/j.isci.2021.102489
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of antibodies to SARS-CoV-2 between asymptomatic and convalescent patients

Abstract: Highlights 60,000 asymptomatic individuals were assessed for SARS-CoV-2 antibody responses Increased Spike IgG correlates with antibody diversity and ACE2 binding inhibition COVID-19 patients had lower antibody responses compared with high asymptomatic responders Individuals can mount diverse immune responses to COVID-19 without symptoms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…OD 490 value less than 0.45 was defined as negatives, while OD 490 value of 0.45 or higher was defined as asymptomatic positives. Detail description of the SARS-CoV-2 spike protein assays used to classify negatives and asymptomatic positives for the same study cohort is reported in our recent publication 59 . However, in this study we only included values of OD 490 ≥ 1 as asymptomatic positive, while the asymptomatic positive OD 490 values between 0.45 and 1 were excluded since they were categorized as low positives.…”
Section: Methodsmentioning
confidence: 99%
“…OD 490 value less than 0.45 was defined as negatives, while OD 490 value of 0.45 or higher was defined as asymptomatic positives. Detail description of the SARS-CoV-2 spike protein assays used to classify negatives and asymptomatic positives for the same study cohort is reported in our recent publication 59 . However, in this study we only included values of OD 490 ≥ 1 as asymptomatic positive, while the asymptomatic positive OD 490 values between 0.45 and 1 were excluded since they were categorized as low positives.…”
Section: Methodsmentioning
confidence: 99%
“…First, to prove whether this phenomenon is specific to inactivated vaccines, related data on the immune persistence and effectiveness of mRNA vaccines, adenovirus vaccines, and subunit vaccines are needed. Second, some studies have reported the immune memory characteristics of convalescent patients 9 , some studies have compared the characteristics of antibody responses in asymptomatic and symptomatic infected people or convalescent patients, 10,11 and some researchers have demonstrated that memory plasma cells in bone marrow may play a key role in immune persistence. 12 The characteristics of the immune system after vaccination are still unclear, and in-depth studies on antibody…”
Section: Some Vaccines Have Obtained Emergency Use Authorization (Eua)mentioning
confidence: 99%
“…The RBD of the S-protein mediates the entry into human cells by binding the angiotensin-converting enzyme 2 (ACE-2) receptor ( Di Nardo et al, 2021 ). Positive correlation between anti-RBD immunoglobulin G (IgG) antibody levels and the inhibition of ACE2 binding and neutralizing antibodies has been described ( Ni et al, 2020 , Suhandynata et al, 2021 , Dwyer et al, 2021 ). It is suggested that the determination of anti-RBD IgG antibodies could be a good marker of neutralizing activity ( Dwyer et al, 2021 , Han et al, 2021 , Beaudoin-Bussières et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Positive correlation between anti-RBD immunoglobulin G (IgG) antibody levels and the inhibition of ACE2 binding and neutralizing antibodies has been described ( Ni et al, 2020 , Suhandynata et al, 2021 , Dwyer et al, 2021 ). It is suggested that the determination of anti-RBD IgG antibodies could be a good marker of neutralizing activity ( Dwyer et al, 2021 , Han et al, 2021 , Beaudoin-Bussières et al, 2020 ). However, data in children are still uncertain and great variability has been reported across the few available studies.…”
Section: Introductionmentioning
confidence: 99%